A New Conjugate Gradient for Unconstrained Optimization Based on Step Size of Barzilai and Borwein - Shareef, Salah G.; Ibrahim, Alaa L. (Science Journal of University of Zakho, 2016)
In this paper, a new formula of is suggested for conjugate gradient method of solving unconstrained optimization problems based on step size of Barzilai and Borwein. Our new proposed CG-method has descent condition, sufficient descent condition and global convergence properties. Numerical comparisons with a standard conjugate gradient algorithm show that this algorithm very effective depending on the number of iterations and the number of functions evaluation.